2020
DOI: 10.1002/path.5375
|View full text |Cite
|
Sign up to set email alerts
|

p53 immunohistochemistry is an accurate surrogate for TP53 mutational analysis in endometrial carcinoma biopsies

Abstract: TP53 mutations are considered a surrogate biomarker of the serous‐like ‘copy number high’ molecular subtype of endometrial carcinoma (EC). In ovarian carcinoma, p53 immunohistochemistry (IHC) accurately reflects mutational status with almost 100% specificity but its performance in EC has not been established. This study tested whether p53 IHC reliably predicts TP53 mutations identified by next‐generation sequencing (NGS) in EC biopsy samples for all ECs and as part of a molecular classification algorithm after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
201
5
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 214 publications
(232 citation statements)
references
References 33 publications
23
201
5
3
Order By: Relevance
“…These non-hotspot TP53 mutations appear to not always impact the expression and function of p53. This is in line with Singh et al [15], where a high proportion of cases with such a TP53 variant and p53 wild-type staining pattern were identified in multiple-classifier ECs.…”
Section: Clinical Outcome Of Multiple-classifier Ecs Versus Single-clsupporting
confidence: 92%
“…These non-hotspot TP53 mutations appear to not always impact the expression and function of p53. This is in line with Singh et al [15], where a high proportion of cases with such a TP53 variant and p53 wild-type staining pattern were identified in multiple-classifier ECs.…”
Section: Clinical Outcome Of Multiple-classifier Ecs Versus Single-clsupporting
confidence: 92%
“…p53 IHC has proved to be a very reliable surrogate marker for detecting underlying TP53 mutations in EC, with reported sensitivity and specificity of 0.96 and 1.00, respectively. [48][49][50] Importantly, several studies have shown that patients with p53mut EC, independent of histotype, grade or stage, show poor clinical outcomes. 5,21,23,29,45 The number of lowgrade EC which fall into the p53mut EC subgroup is limited, but the available data point towards unfavourable clinical outcomes in these cases.…”
Section: H O W D O E S T H E P R E S E N C E O F a T P 5 3 M U T A Tmentioning
confidence: 99%
“…2 Mismatch repair protein (MMR) deficiency is defined by the loss of one or more MMR‐proteins (MLH1, PMS2, MSH2 and MSH6). 3 p53 immunohistochemistry (IHC) is an acceptable surrogate marker for TP53 mutational status in MMR‐proficient, POLE wild‐type endometrial cancer (EC) …”
Section: Introductionmentioning
confidence: 99%
“…Targeted tagged amplicon deep sequencing (TAm-Seq) as described [19] on an Illumina MiSeq or HiSeq4000 using PE-150bp protocol was performed for a previous study (13). The entire coding region for PTEN was included in the targeted panel.…”
Section: Pten Sequencingmentioning
confidence: 99%